Lattice dynamics, Thermodynamic functions, and phase transitions of p-dichloro-and 1, 2, 4, 5 tetrachlorobenzene. - Bonadeo, H.; D'Alessio, E.; Halac, E.; Burgos, E. (American Institute of Physics, 1978)
Fil: Bonadeo, H. Comisión Nacional de Energía Atómica; Argentina